Recommendations for Traceability and Use of USDA Premise ID’s for Swine Exhibition at Terminal Shows in Florida - Heidi M. Hill; Morgan T. McKinney; T. Langford; Clayton T. Roland; Charles Carr; Pamela Hunter (EDIS, 2018)
Animal disease traceability has become an increasingly important topic within animal agriculture. Florida's breeders are encouraged to apply premise ID before marketing pigs to youth who will exhibit in terminal shows to assist with traceability. If pigs do not already have a premise ID tag, personnel from that terminal show should apply a plastic premise ID tag associated with that particular fair.